(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Nicotine in cigarettes Stimulates the release of the hormone adrenaline thereby increasing blood pressure. Hypertension or Increase. blood pressure increases the pressure in the left ventricular muscle roomates Appears as hypertrophy. then an increase is in left atrial pressure Followed by left atrial dilatation space. Hypertensive people who smoke cause disruption of the process of ventricular de polarization and re polarization of the heart. This study aims to analyze hypertension with left atrial abnormalities, left ventricular hypertrophy, and QT interval in smokers at Tower Hanyar Health Center. The observational study design uses descriptive method with cross sectional design. The sample consisted of 60 research subjects and was divided into two groups, namely the group of smokers with hypertension with a total of 30 people and the group of non-hypertensive smokers with the number of 30 people Obtained by consecutive sampling method. In the study found the relationship of hypertension with left atrial abnormalities, left ventricular hypertrophy and QT interval in smokers tested the hypothesis with Chi-square test with a confidence level of 95%, with ap value = 0.00. The results of the analysis of PROVE that there is a relationship of hypertension with left atrial abnormalities, left ventricular hypertrophy and left the QT interval in smokers at Tower Hanyar Health Center. left ventricular hypertrophy and QT interval in smokers tested the hypothesis with Chi-square test with a confidence level of 95%, with ap value = 0.00. The results of the analysis of PROVE that there is a relationship of hypertension with left atrial abnormalities, left ventricular hypertrophy and left the QT interval in smokers at Tower Hanyar Health Center. left ventricular hypertrophy and QT interval in smokers tested the hypothesis with Chi-square test with a confidence level of 95%, with ap value = 0.00. The results of the analysis of PROVE that there is a relationship of hypertension with left atrial abnormalities, left ventricular hypertrophy and left the QT interval in smokers at Tower Hanyar Health Center.